Education through the lens of sustainable human development - Gianna Alessandra Sanchez Moretti (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
If human development is defined as a comprehensive economic, social, cultural and political process aiming to improve the well-being of populations and individuals, then the one element that can serve as the motor driving development is education. However, it is alleged that the international community and governments worldwide do not yet recognise the full potential and transformative power of education as a catalyst for human development, even if education is indeed considered a fundamental human right. [...]
Keywords: 330; sustainable human development; education; right to education; inequalities; discrimination